2011
DOI: 10.1097/ogx.0b013e318216819a
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plurality and Obesity on Betamethasone Concentrations in Women at Risk for Preterm Delivery

Abstract: Objective-Antenatal corticosteroids (ACS) decrease respiratory distress syndrome in singleton gestations. Twin data is less clear. Obesity and BMI also affect medication distribution volume. We evaluated whether maternal or neonatal cord betamethasone concentrations differed in twin gestations or in obese patients.Study Design-Participants receiving betamethasone in a randomized controlled trial of weekly ACS were identified. We analyzed maternal delivery and cord serum betamethasone concentrations comparing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 3 publications
0
21
0
1
Order By: Relevance
“…In the present trial, the BetaP plus BetaA regimen caused even longer adrenal suppression. Our results showing sustained concentrations of Beta following BetaP plus BetaA are not unique but are underappreciated by the field …”
Section: Discussionmentioning
confidence: 64%
“…In the present trial, the BetaP plus BetaA regimen caused even longer adrenal suppression. Our results showing sustained concentrations of Beta following BetaP plus BetaA are not unique but are underappreciated by the field …”
Section: Discussionmentioning
confidence: 64%
“…The incidence of multiple pregnancies has been increasing in the past 4 decades [9,10], and twins are at increased risk of preterm birth, making administration of prenatal glucocorticoids more likely. However, the effect of glucocorticoids on prenatal lung maturation in multiple pregnancies remains unclear because trials in twins are limited and evidence is lacking [1,11–16].…”
Section: Introductionmentioning
confidence: 99%
“…Gyamfi et al. found that maternal and umbilical cord serum betamethasone concentrations at delivery were similar in singleton and twin gestations, suggesting that any decrease in effectiveness is not due to inadequate fetal drug levels. The most likely reason that twins have not demonstrated improvement following steroids is probably related to the small sample size of the randomized controlled trials, which gives them insufficient power to confirm a difference.…”
Section: Resultsmentioning
confidence: 99%
“…A large population‐based study examined RDS in singleton, twin, and triplet gestations exposed to corticosteroids with delivery at 24–32 weeks (Figure ). Corticosteroids reduced the risk of RDS in both twins and triplets but the benefit was less than with singletons.…”
Section: Resultsmentioning
confidence: 99%